The Relationship Between Sleep Duration and Life Satisfaction in Middle-aged and Older Adults: evidence from China - Hao, Chao; Xie, Feiyang; Bu, Naifeng; Wang, Xue (Journal of Psychological Perspective, 2026)
Aging is becoming increasingly common worldwide, which has a profound impact on the social structure, making it imperative to enhance the life satisfaction of the middle-aged and older adults. While life satisfaction serves as a crucial metric for assessing quality of life in aging societies, empirical evidence suggests improvement lags behind advancements in medical technology and living standards. Thus, identifying the key factors influencing their life satisfaction is crucial. We employed data from 12,525 validated samples from the 2020 China Health and Retirement Longitudinal Study to examine sleep's impact on life satisfaction through multiple mediation modeling. The findings revealed that insufficient sleep emerged as a widespread phenomenon significantly compromising the life satisfaction of the middle-aged and older adults. Physical health and depressive symptoms mediated 85% of sleep's total effect, with depressive symptoms alone accounting for 65% of the mediation. The disproportionate mediation effect of depressive symptoms highlights mental health's critical role in the well-being assessment of the middle-aged and older adults.